PEMBERIAN SCAFFOLDING BERDASAR PELEVELAN TAKSONOMI SOLO SISWA KATEGORI UNISTRUCTURAL DALAM MENYELESAIKAN SOAL JARAK DIMENSI TIGA - Fitri Umardiyah; M. Farid Nasrulloh (Universitas Lambung Mangkurat, 2021)
Taksonomi SOLO merupakan cara menglasifikasi kemampuan siswa dalam mengerjakan soal geometri. Siswa yang termasuk kategori unistructural dalam pelevelan Taksonomi SOLO, mampu mengunakan satu informasi/konsep dalam pengerjaan soal. Berdasar hasil wawancara dengan guru matematika di MA Bahrul Ulum Tambakberas Jombang, siswa kesulitan mengintepretasikan materi jarak dimensi tiga ke dalam pikiran mereka. Siswa membutuhkan bantuan (scaffolding) untuk meningkatkan level kemampuannya. Penelitian ini bertujuan untuk mendapatkan deskripsi mengenai pemberian scaffolding yang dapat meningkatkan level taksonomi SOLO siswa kategori unistructural sesuai dengan kebutuhan siswa. Subjek penelitian terdiri atas lima siswa kelas XII yang terpilih melalui tes penglasifikasian Taksonomi SOLO level unistructural. Penelitian ini merupakan penelitian deskriptif. Peneliti sebagai instrumen utama menganalis hasil pengerjaan tes siswa dan melakukan wawancara mendalam. Scaffolding diberikan kepada siswa dengan mengacu pada hasil tes dan wawancara. Scaffolding diberikan agar siswa kategori unistructural dapat menggunakan lebih dari satu informasi/konsep dan saling mengaitkan antar konsep agar mampu membuat kesimpulan yang relevan. Scaffolding yang dapat meningkatkan level Taksonomi SOLO siswa adalah scaffolding level 2 yaitu explaining (showing and telling), reviewing (students explaining and justifying; looking, touching and verbalising; prompting and probing questions; parralel modeling ), restructuring (negotiating meanings), dan scaffolding level 3 yaitu developing conceptual thinking (making connections). Kata kunci: scaffolding, taksonomi solo, unistructural, jarak dimensi tiga Abstract: SOLO Taxonomy is one way to classify students's abilities in working on geometry’s problems. Students who are included in the unistructural category in the SOLO Taxonomy level are able to use one information / conept in solving problems. Based on result of interview with mathematics teachers at MA Bahrul Ulum Tambakberas Jombang, students had difficulty when interpreting distance material in solid geometry into their minds. Students who have difficulty need help (scaffolding) to increase their level of ability. This study aims to obtain a description of the provision of scaffolding that can increase the SOLO taxonomy level of students in the unistructural category according to student needs. Participants are five student of class 12th who is selected by test. This research uses a descriptive qualitative approach. Researchers as the main instrument analyze the results of student tests and conduct in-depth interviews with students. The test and interview results are used as a reference in providing scaffolding to students. Sacffolding is given so that students in the unistrutural category can use more than one information / concept and link each other between concepts in order to be able to make relevant conclusions. Scaffolding that can increase the level of SOLO’ to solve geometry problems is scaffolding level 2, namely explaining (showing and telling), reviewing (students explaining and justifying; looking, touching and verbalising; prompting and probing questions; parralel modeling), restructuring (negotiating meanings), and level 3 scaffolding, namely developing conceptual thinking (making connections). Keywords: scaffolding, SOLO taxonomy, unistructural, distance in solid geometry